Spinoza’s Philosophy of Affects - Bačani, Nina (Analiza: časopis za kritično misel, 2025)
In his Ethics (1677), Spinoza defends monism – the idea that there exists a single substance that is identical with God and nature. Mind and body are its expressions, which we perceive as two distinct attributes (of the same substance): thought and extension. Spinoza’s philosophy of affects (developed in Parts Three and Four of the Ethics) focuses on understanding human emotions as natural phenomena governed by the universal laws of nature. According to Spinoza, a person who does not master their affects is a slave to fate, while freedom can be achieved through the guidance of reason. He distinguishes between active and passive affects: active affects arise from reason and enhance a person’s power, whereas passive affects diminish their capacity to act. Spinoza’s philosophy offers a theoretical framework for understanding emotions that was revolutionary for his time and remains influential even in contemporary psychological and neuroscientific research.
Keywords: Spinoza; monism; affects; freedom; psychology